2015
DOI: 10.20452/pamw.3156
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of probiotics in type 2 diabetes: a meta-analysis

Abstract: INTROduCTION An increasing number of studies suggest that the use of probiotics may have a beneficial effect in patients with type 2 diabetes.ObjECTIvEs The aim of the study was to assess the ability of probiotics to modify selected cardiometabolic risk factors in subjects with type 2 diabetes.METhOds PubMed, Embase, Cochrane Library, and Scopus databases were thoroughly reviewed up to January 2015 to search for randomized controlled trials (RCTs) that examined the effect of probiotics on selected modifiable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
1
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(64 citation statements)
references
References 7 publications
2
53
1
7
Order By: Relevance
“…Many studies have assessed the effect of probiotics on metabolic profiles in people [39], and several systematic reviews and meta-analyses have shown that probiotics had an effect on diabetes, but their pooled results showed a lack of accordance and their included studies were uncomprehensive, which could lead to a possibility of unreliable results and conclusions [27][28][29]. Thus, we performed this meta-analysis demonstrate the effects of probiotics for T2DM and other MS patients in reducing the level of fasting glucose, insulin and HbA 1c .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have assessed the effect of probiotics on metabolic profiles in people [39], and several systematic reviews and meta-analyses have shown that probiotics had an effect on diabetes, but their pooled results showed a lack of accordance and their included studies were uncomprehensive, which could lead to a possibility of unreliable results and conclusions [27][28][29]. Thus, we performed this meta-analysis demonstrate the effects of probiotics for T2DM and other MS patients in reducing the level of fasting glucose, insulin and HbA 1c .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some of the studies have not shown a positive curative effect and their conclusions still remain controversial, for some studies gave negative results [12,22]. Previous systematic reviews and meta-analyses have shown that probiotics had an effect on diabetes, but their pooled results showed a lack of accordance and their included studies were uncomprehensive, which could lead to a possibility of unreliable results and conclusions [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the SCFAs, produced by the beneficial gut microbes, may prevent low-grade inflammation via maintaining intestinal integrity [35]. A meta-analysis of the ability of probioticsintervention to reduce CRP levels, in type 2 diabetes, showed an overall non-significant effect [35].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of the ability of probioticsintervention to reduce CRP levels, in type 2 diabetes, showed an overall non-significant effect [35]. A sub-group analysis in another metaanalysis suggested, however, that a high probiotic dose, longer intervention duration, and the use of multiple strains of probiotics would, indeed, have anti-inflammatory effects [36].…”
Section: Discussionmentioning
confidence: 99%
“…4 A growing body of evidence suggests that favorable associations exist between probiotic consumption and metabolic profile among diabetes subjects. 5 However, the potential mechanisms secretion from enteroendocrine L-cells to improve carbohydrate metabolism, decrease glucotoxicity and increase insulin sensitivity of target cells. 6 Other proposed mechanisms to explain the action of probiotics on diabetes relate to anti-inflammatory, antioxidant and immunomodulatory effects and alteration of the expression of some genes involved in diabetes.…”
Section: Introductionmentioning
confidence: 99%